Clinical evidence for a lack of cross-resistance between temsavir and ibalizumab or maraviroc. (1st January 2022) - Rose, Ronald; Gartland, Margaret; Li, Zhufang; Zhou, Nannan; Cockett, Mark; Beloor, Jagadish; Lataillade, Max; Ackerman, Peter; Krystal, Mark
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Temsavir (TMR), the active agent of the gp120-directed attachment inhibitor fostemsavir (FTR), the CD4-directed attachment inhibitor ibalizumab (IBA), and the CCR5 antagonist maraviroc (MVC) are antiretroviral agents that target steps in HIV-1 viral entry. Although mechanisms of inhibition of the three agents are different, it is important to understand whether there is potential for cross-resistance between these agents, as all involve interactions with gp120. Methods: Envelopes derived from plasma samples from participants in the BRIGHTE study who experienced protocol-derived virologic failure (PDVF) and were co-dosed with FTR and either IBA or MVC were analyzed for susceptibility to the agents. Also, CCR5-tropic MVC-resistant envelopes from the MOTIVATE trials were regenerated and studies were performed to understand whether susceptibility to multiple agents were linked. Results: The cloned envelopes exhibited reduced susceptibility to TMR and resistance to the co-dosed agent. At PDVF, emergent or preexisting amino acid substitutions were present at TMR positions of interest. When amino acid substitutions at these positions were reverted to the consensus sequence, full susceptibility to TMR was restored without effecting resistance to the co-dosed agent. In addition, five envelopes from MOTIVATE were regenerated and exhibited R5-tropic-MVC-resistance. Only one exhibited reduced susceptibility to TMR and it contained an M426L polymorphism. When reverted to 426M, full sensitivity for TMR was restored, but it remained MVC resistant. Conclusion: The data confirm that decreased susceptibility to TMR and resistance to IBA or MVC are not linked and that there is no cross-resistance between either of these two agents and FTR.